Alzheimer's disease: An update - Kumar V.; Singh P.N.; Singh H.K. (My University, 2025)
Alzheimer's disease begins with the loss of short-term memory, followed by progressive dementia which involves memory loss, impairment of intellectual functioning, judgement and decision making. It is the most common cause of dementia in adults in north America and Europe. At present there is no effective treatment to prevent or ameliorate the progression of Alzheimer's disease, which is the commonest cause of dementia in the elderly. The characteristic neuropathological hallmarks of Alzheimer's disease are β/A4 - containing plaques, neurofibrillary tangles and amyloid infiltration of cerebrovascular walls. Understanding of the biological basis of cognitive disorders is undergoing rapid advancement. The research progress and hypothesis about the brain abnormalities underlying Alzheimer's disease such as amyloid cascade hypothesis, cholinergic theories and excitotoxic hypothesis are discussed in the present article. Inspite of this, various treatments for Alzheimer's disease such as cognitive enhancers, metabolic enhancers, vitamins and hormones, neuropeptides, psychostimulants etc. including other current approaches viz. growth factors, transplantation of neuronal tissue and immunisation with amyloid-β peptide are also discussed. However, novel methods for delivering these molecules into the brain requires to be developed before launching their clinical trails.